Pulmonary vein isolation for paroxysmal atrial fibrillation using high-power short duration radiofrequency or second-generation cryoballoon ablation. (24th May 2021) - Kardos, A; Kassa, K; Nagy, Z; Kis, Z; Simkovits, D; Som, Z; Csakany, L; Major, T; Foldesi, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Differences in the left atrial (LA) tissue loss can occur following different pulmonary vein isolation (PVI) techniques. Purpose: Our prospective study compared the biomarker, the LA mechanical, and the electrophysiological findings as indicators of LA myocardial damage after a high-power short duration (HPSD) with contact force radiofrequency catheter and second-generation cryoballoon (CB2) ablation of paroxysmal atrial fibrillation (AF). Methods :We enrolled 40 patients with paroxysmal AF [16 (40%) women, mean age = 55.9 ± 12.4 years] who underwent HPSD (n = 21) or CB2 (n = 19). Biomarker levels (hs-cTnT, CK-MB, hs-CRP, LDH) and the transport function of the LA by transthoracic echocardiography (TTE) were compared pre and post procedurally. High-density mapping (HDM) was performed in sinus rhythm using a multielectrode diagnostic catheter in each group to define isolated left atrial low voltage area (LVA; <0.2mV in bipolar voltage mapping). LA CT-angiography and HDM merge was used to calculate the post-PVI LVA and the LVA/LA surface ratio. Results: Postablation hs-cTnT and hs-CRP levels were comparable in the ablation groups (HPSD: 1249 ± 469 and 9.53 ± 10.30 vs. CB2: 995 ± 280 and 12.36 ± 5.76, p = 0.065 and p = 0.732), while CK-MB and LDH levels were significantly higher following CB2 ablation (HPSD: 6.61 ± 2.62 and 349.9 ± 65.6 vs. CB2: 26.01 ± 6.88 and 451.6 ± 91.3, p < 0.001 and p < 0.001). The transport function of the LA did not change significantly by TTE after the procedure. Fractional Area Change at baseline and 3 months was 33.9 ± 13.8 and 33.5 ± 10.7 p = 0.9 in the HPSD group while 38.1 ± 8.6 and 35.3 ± 12.2 p = 0.9 in the CB2 group. LA Ejection Fraction measured in the two groups (before and 3-month post-procedure): HPSD: 51.2 ± 20.5% and 49.5 ± 14.7%, p = 0.9, CB2: 49.7 ± 15.5% and 50.7 ± 13.3%, p = 0.8). Ablation time was comparable in the two groups (HPSD: 1676 ± 570 sec, CB2: 1495 ± 494 sec, p = 0.279), while fluoroscopy time and radiation exposure were significantly higher in the CB2 group (HPSD: 5.62 ± 4.31 min and 232 ± 406 cGycm2, CB2: 13.65 ± 5.18 min and 1819 ± 1669 cGycm2, p <0.001 and p <0.001). The LVA/LA surface ratio were: HPSD group: 8.37 ± 6.42% and CB2 group: 13.58 ± 8.92% (p = 0.007). At 12-month follow-up, the success rate, defined as freedom from AF/atrial tachycardia without antiarrhythmic drug was 80.1% (HPSD) and 84.2% (CB2) respectively. Conclusions: The LA scar tissue was significantly higher following CB2 ablation, but did not affect medium-term efficacy. However, tissue loss did not reduce the transport function of the LA.